Orthopaedic Surgeon - Wolff, Andrew B. (Orthop J Sports Med, 2017)
OBJECTIVES: Results of revision labral repair and labral debridement of irreparable issue have been poor. A circumferential labral reconstruction (CLR) with ITB allograft between the transverse acetabular ligament antero-inferiorly to the 7-8 o’clock position postero-inferiorly eliminates any tissue damaged beyond repair, restores stability and eliminates any high stress junction points. This study seeks to compare outcomes with this technique relative to our patients with hip problems that are reliably fixed with simple labral repair. METHODS: We retrospectively examined 34 consecutive patients undergoing arthroscopic surgery of the hip with CLR with a fascia lata allograft and compared them with 49 consecutive patients undergoing simple labral repair during the same 4 month period. Pre- and post-op surveys included Visual Analog Pain Score (VAS), International Hip Outcome Tool (IHOT-12), modified Harris Hip Score (mHHS), 12-item Short Form Health Survey (SF-12) and Hip Outcome Score (HOS-ADL and HOS-SSS). Pre-op Tonnis grade was recorded. Severity of labral damage was evaluated in separate sidearm study of 20 patient videos not involved in current study to assess intra-observer reliability for grading of severity of labral damage. RESULTS: The mean age of the reconstruction patients was 43.0 vs. 29.1 for the repair patients (p<0.001). The repair group had 45% mild and 55% moderate tears; the CLR group had 80% severe tears or segmental defects and 20% moderate tears. 3.9% of the repair group were revision procedures, while 35% of the CLR group were revision procedures. Pre-op Tonnis grade in the CLR group was 0.44 vs. 0.11 (P<0.001). Follow-up rate was 82% with a minimum follow-up of 23 months (range: 23-28 months). In the CLR group, 5 patients failed; 1 for core muscle repair procedure, 2 went on to subsequent hip arthroplasty, 2 in need of hip arthroplasty. All 4 conversions to arthroplasty had pre-op tonnis grade of 2. 3 procedures failed in the repair group with one subsequent core muscle repair and 2 revisions to labral reconstruction. In the reconstruction group, the mean Pain VAS score decreased from 4.78 preoperatively to 1.9 postoperatively (P<0.001), IHOT-12 scores increased from 32.38 to 68.9 (P<0.001), and mHHS increased from 48.67 to 74.63 (P<0.001). The SF-12 survey exhibited an increase from 36.29 to 43.15 (P=0.028), HOS-ADL scores increased from 56.28 to 87.47 (P<0.001), and HOS-SSS scores increased from 32.40 to 68.55 (P=0.0028). These improvements were not statistically different from those observed in the repair group (Pain VAS: P=0.361; HOS-ADL: P=0.314; HOS-SSS: P=0.288; mHHS: P=0.996; IHOT: P=0.192; SF: P=0.642). Intra-observer reliability of sidearm video study Kappa = 0.66 indicating moderately good reliability in the grading of severity of labral damage. CONCLUSION: This study shows that patients undergoing circumferential labral reconstruction with ITB allograft exhibit favorable outcome at 2 years postoperatively with respect to pain and activities of daily living—comparable to the results achieved in patients undergoing repairs of labra with lower severity of damage in a more challenging patient population (14 yrs older with far worse labral damage, a higher Tonnis grade, and far higher percentage of revisions). These data suggest that circumferential arthroscopic labral reconstruction is a viable option for patients with missing or severely compromised labral tissue.